The Effect of Foliar Application of oil palm empty fruit bunch (OPEFB) ash nanoparticles on Stomata Anatomy of Potato Leaf Plants (Solanum tuberosum L.) - Mulyono, Mulyono; Febriana, Erlintang Ratri; Hidayat, Taufiq (PLANTA TROPIKA, 2022)
The productivity of potatoes (Solanum tuberosum L.) in Indonesia is still low. Fertilization needs to be done to increase potato productivity. This study aimed to examine the effects of applying oil palm empty fruit bunch (OPEFB) ash nanoparticles on the anatomy of potato stomatal and leaf cells (Solanum tuberosum L.). The research was carried out from March to June 2021 in the Sumberejo Village, Ngablak District, Magelang Regency, Central Java, and at the Agrobiotechnology Laboratory, Faculty of Agriculture, University of Muhammadiyah Yogyakarta. The study used a single-factor treatment design with a Randomized Completely Block Design (RCBD). The treatments tested included the foliar application of OPEFB ash nanoparticles at several concentration, consisting of 0% (control), 0.1%, 0.2%, 0.3%, and 0.4%. The results showed that foliar application of nanoparticles OPEFB ash affected stomatal anatomy, namely guard cell width, stomatal aperture, and density. The application of OPEFB ash nanoparticles with a concentration of 0.3% was most effective in increasing the opening of stomata because it affects the activity of the photosynthetic process.